My mama says there aren't any zombies, ghosts, vampires, creatures, demons, monsters, fiends, goblins, or things - Viorst, Judith (Atheneum, 1973)
If his mother has made other important mistakes, can Nick trust her word that there are no goblins and such lurking around in the night?